Cobalt(II)–catalyzed C8H alkoxylation of 1-naphthylamine derivatives with alcohols. Issue 11 (15th March 2019) - Zhang, Tingfang; Zhu, Hongmei; Yang, Fan; Wu, Yusheng; Wu, Yangjie
Abstract: An efficient protocol for cobalt (II)-catalyzed regioselective aryl C8H bond alkoxylation of 1-naphthylamine derivatives with readily available alcohols has been developed, demonstrating an efficient approach to 8-alkoxy-1-naphthylamine derivatives with good functional group tolerance. Note that the picolinamide moiety as a bidentate directing group may play a key role in this regioselective transformation. Graphical abstract: An efficient protocol for cobalt (II)-catalyzed regioselective aryl C8H bond alkoxylation of 1-naphthylamine derivatives with readily available alcohols has been developed, demonstrating an efficient approach to 8-alkoxy-1-naphthylamine derivatives with good functional group tolerance. Note that the picolinamide moiety as a bidentate directing group may play a key role in this regioselective transformation.Image 1